2001
DOI: 10.1137/s0097539700366115
|View full text |Cite
|
Sign up to set email alerts
|

Traveling Salesman-Based Curve Reconstruction in Polynomial Time

Abstract: Abstract. An instance of the curve reconstruction problem is a finite sample set V of an unknown collection of curves γ. The task is to connect the points in V in the order in which they lie on γ. Giesen [Proceedings of the 15th Annual ACM Symposium on Computational Geometry (SCG '99), 1999, pp. 207-216] showed recently that the traveling salesman tour of V solves the reconstruction problem for single closed curves under otherwise weak assumptions on γ and V ; γ must be a single closed curve. We extend his re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Althaus and Mehlhorn [2] show that the traveling salesman path/tour can be computed in polynomial time for dense samples from plane curves, satisfying the regularity conditions we specified in this paper.…”
Section: Fie(s)ne'(s) = Idementioning
confidence: 71%
“…Althaus and Mehlhorn [2] show that the traveling salesman path/tour can be computed in polynomial time for dense samples from plane curves, satisfying the regularity conditions we specified in this paper.…”
Section: Fie(s)ne'(s) = Idementioning
confidence: 71%
“…For example, reconstructing a curve from a set of measured points is a fundamental variant of an important family of image processing problems. In [47] an apparently expensive method based on the travelling salesman problem is investigated. Experiments indicated that "reasonable" inputs lead to easy instances of the travelling salesman problem.…”
Section: Methodsmentioning
confidence: 99%
“…Dey et al [7] proposed an algorithm that constructs a polygonal reconstruction from any set of input points that is not a dense sample of the closed smooth curve. According to Althaus and Mehlhorn [8], the problem of curve reconstruction is a finite sample of unknown curves [8]. To solve this problem, one has to connect the points in the unknown curve in the order in which they lie.…”
Section: Studies About Point Clouds Without Noisementioning
confidence: 99%